2019
DOI: 10.1186/s12870-019-2212-1
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of citrus UDP-GLUCOSYL TRANSFERASE gene enhances anthocyanin and proanthocyanidins contents and confers high light tolerance in Arabidopsis

Abstract: BackgroundCitrus fruits are consumed freshly or as juice to directly provide various dietary flavonoids to humans. Diverse metabolites are present among Citrus genera, and many flavonoids biosynthetic genes were induced after abiotic stresses. To better understand the underlying mechanism, we designed experiments to overexpress a UDP-GLUCOSYL TRANSFERASE gene from sweet orange (Citrus sinensis) to evaluate its possible function in metabolism and response to stress.ResultsOur results demonstrated that overexpre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 66 publications
1
34
0
Order By: Relevance
“…The plants with higher antioxidant activity or capacity show more resistance against drought stress [52], and those with lower antioxidant activity or capacity are susceptible to drought stress [53]. Prolonged exposure to drought and high light stress enhanced antioxidant activity and capacity in citrus plants [54,55]. In our experiments, increased exposure to drought stress of poplar plants also increased their antioxidant capacity and activity (Figure 6A−B).…”
Section: Discussionsupporting
confidence: 54%
“…The plants with higher antioxidant activity or capacity show more resistance against drought stress [52], and those with lower antioxidant activity or capacity are susceptible to drought stress [53]. Prolonged exposure to drought and high light stress enhanced antioxidant activity and capacity in citrus plants [54,55]. In our experiments, increased exposure to drought stress of poplar plants also increased their antioxidant capacity and activity (Figure 6A−B).…”
Section: Discussionsupporting
confidence: 54%
“…Besides that, anthocyanin has a photoprotective effect on the PSII [27]. It has been reported that Arabidopsis confers a better antioxidant potential and tolerance to high irradiation stress by increasing the anthocyanin content [28]. The moth orchid is highly sensitive to high irradiation because whenever the light intensity is above 300 µmol m −2 s −1 , the ETR and qP levels were significantly reduced (Figure 1), indicating damage to PSII.…”
Section: Bl100 Induces Photo-acclimation In Moth Orchidmentioning
confidence: 92%
“…(2019) 27 CsCYP75B1 Sweet orange A. thaliana Flavonoid biosynthesis Rao et al. (2020) 28 CsUDP78D3 Sweet orange A. thaliana Anthocyanin Rao et al. (2019b) 29 CgRuby1 , CgRuby2 , AbRuby2 Atalantia and pummelo A. thaliana Huang et al.…”
Section: Key Genes Associated With Citrus Domestication and Their Impmentioning
confidence: 99%